A Xenopus ribosomal protein S6 kinase has two apparent kinase domains that are each similar to distinct protein kinases. - Jones, S W (1988)
We report the molecular cloning of cDNAs for S6 kinase II (S6KII) mRNAs present in Xenopus ovarian tissue. Two cDNAs were isolated by hybridization to oligonucleotide probes designed to encode tryptic peptides isolated from S6KII. The two cDNAs show 91% sequence similarity to each other. These two cDNAs predict proteins of 733 (S6KII alpha) and 629 (S6KII beta) amino acids that show 95% sequence similarity over the 629 amino acids where they are colinear. Amino acids 44-733 of S6KII alpha were expressed in Escherichia coli and the recombinant protein was used to raise antiserum in rabbits. This antiserum reacted with authentic S6KII prepared from Xenopus eggs. This interaction was specifically blocked by the recombinant protein from E. coli. The sequences of S6KII alpha and -beta predict four tryptic peptides whose sequences are identical to four peptides isolated from a tryptic digest of S6KII. The S6KII proteins have a very unusual structure when compared with previously studied protein kinases. They contain two apparent kinase domains, each similar to distinct protein kinases. The amino-terminal 366 amino acids show high sequence similarity to the regions of protein kinase C, the catalytic subunit of cAMP-dependent protein kinase, and cGMP-dependent protein kinase that contain the sites for ATP binding and are believed to be the catalytic centers for phosphotransferase activity. The remainder of the S6 kinase molecule shows high sequence similarity to the ATP-binding and presumed catalytic domain of the catalytic subunit of phosphorylase b kinase.